(untitled) (Journal of Parents and Teachers, 2013)
Célestine Freinet was a pedagogue and one of the forerunners in the movement called “ New School”. Its pedagogy is based on the opposition to the education system of the time, that is to say, a popular school where everybody could attend classes. The students would be in touch with the environment and, in this way; the quality of education would increase. He defended three key principles: materials and techniques used in class, the second principle was cooperative life, organization and work assessment and the last one was based on individualised learning that is to say that, as every student learns in a different way, everybody should have a different learning plan.